1987
DOI: 10.1159/000146423
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin Gene-Related Peptide in Morphologically Well-Defíned Type II Neurons of the Enteric Nervous System in the Porcine Small Intestine

Abstract: The morphological classification of the different neuronal cell types is generally accepted and expanded by us; nevertheless, immunohistochemically and electrophysiologically the existence of clear-cut categories of enteric neurons is frequently questioned. The immunohistochemical results demonstrated in this study, however, provide the first direct link between a morphological type of enteric neuron and an immunohistochemical staining for a distinct peptide. Evidence demonstrates that calcitonin gene-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 2 publications
4
31
0
Order By: Relevance
“…CGRP is present in enteric type II neurons of several species, including pig, mouse, and sheep (Scheuermann et al, 1987;Furness et al, 2004b;Chiocchetti et al, 2006). It has been suggested that these neurons represent the IPANs (see above) and CGRP may be involved as a cotransmitter in afferent, enteric pathways (Grider, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CGRP is present in enteric type II neurons of several species, including pig, mouse, and sheep (Scheuermann et al, 1987;Furness et al, 2004b;Chiocchetti et al, 2006). It has been suggested that these neurons represent the IPANs (see above) and CGRP may be involved as a cotransmitter in afferent, enteric pathways (Grider, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In the guineapig myenteric plexus, most of type II neurons exclusively contain the calcium binding protein calbindin Iyer et al, 1988;Costa et al, 1996), which can be used as a marker for myenteric IPANs in this species. In other species, other markers or marker combinations were recommended for immunohistochemical detection of Dogiel type II neurons, which are supposed to represent the IPANs also in these species (Scheuermann et al, 1987;Brehmer et al, 2004a;Furness et al, 2004b;Chiocchetti et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The remainder of the preparative procedure for light anil electron microscopy, aimed at improving the conditions for immunocytochemistry. was initially described by Llewellyn-Smith et al [6] for the small intestine of the guinea pig and applied to the pig by Scheuermann et al (2). Wholemounts consisted either of the serosal layer and longitudinal smooth muscle layer, to which the myenteric plexus was attached, or of the sub mucosal and remaining part of the mucosal layer.…”
Section: Methodsmentioning
confidence: 99%
“…Essential for the identification of a definite enteric neuronal type are special modes of staining that are dis tinctive for one cell type and that display a clear image at the two levels of microscopy. The link between a morpho logical population of enteric neurons and a specific immu nohistochemical reaction was first provided with the lightmicroscopic identification of calcitonin gene-related pep tide (CGRP) as marker peptide for well-defined type II neurons in the enteric nervous system of the porcine small intestine [2]. The type II neuron, first described by Dogiel [3], is well known, but there is controversy about its definition as a multiaxonal.…”
Section: Introductionmentioning
confidence: 99%